"Orphans of the storm" - Griffith, D. W. (David Wark), 1875-1948; Gish, Lillian, 1893-1993; Ennery, Adolphe d', 1811-1899.; D.W. Griffith Corporation; Cinetel Films ([Los Angeles, CA] : D.W. Griffith Productions, 1921)
Two orphaned sisters are caught up in the turmoil of the French Revolution, encountering misery and love along the way. --
Originally released as a motion picture in 1921.
Based on: Les deux orphalines / Adolphe d'Ennery.
Lillian Gish, Dorothy Gish, Joseph Schildkraut, Frank Losee, Katherine Emmet, Lucille La Verne.
Cinematographers, Hendrik Sartov, Paul Allen, G.W. Bitzer; editors, James Smith, Rose Smith; musical arrangements, Louis F. Gottschalk, William Frederick Peters.
Silent film with English intertitles and musical background.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2016); and the IMDb.
Keywords: France -- History -- Revolution, 1789-1799 -- Drama; Silent films; Feature films; Film adaptations; Internet videos; Streaming video